Pentaerythritol Tetranitrate In Vivo Treatment Improves Oxidative Stress and Vascular Dysfunction by Suppression of Endothelin-1 Signaling in Monocrotaline-Induced Pulmonary Hypertension. (28th February 2017) - Steven, Sebastian; Oelze, Matthias; Brandt, Moritz; Ullmann, Elisabeth; Kröller-Schön, Swenja; Heeren, Tjebo; Tran, Lan P.; Daub, Steffen; Dib, Mobin; Stalleicken, Dirk; Wenzel, Philip; Münzel, Thomas; et al.
Abstract : Objective . Oxidative stress and endothelial dysfunction contribute to pulmonary arterial hypertension (PAH). The role of the nitrovasodilator pentaerythritol tetranitrate (PETN) on endothelial function and oxidative stress in PAH has not yet been defined. Methods and Results . PAH was induced by monocrotaline (MCT, i.v.) in Wistar rats. Low (30 mg/kg; MCT30), middle (40 mg/kg; MCT40), or high (60 mg/kg; MCT60) dose of MCT for 14, 28, and 42 d was used. MCT induced endothelial dysfunction, pulmonary vascular wall thickening, and fibrosis, as well as protein tyrosine nitration. Pulmonary arterial pressure and heart/body and lung/body weight ratio were increased in MCT40 rats (28 d) and reduced by oral PETN (10 mg/kg, 24 d) therapy. Oxidative stress in the vascular wall, in the heart, and in whole blood as well as vascular endothelin-1 signaling was increased in MCT40-treated rats and normalized by PETN therapy, likely by upregulation of heme oxygenase-1 (HO-1). PETN therapy improved endothelium-dependent relaxation in pulmonary arteries and inhibited endothelin-1-induced oxidative burst in whole blood and the expression of adhesion molecule (ICAM-1) in endothelial cells. Conclusion . MCT-induced PAH impairs endothelial function (aorta and pulmonary arteries) and increases oxidative stress whereas PETN markedly attenuates these adverse effects. Thus, PETN therapy improves pulmonary hypertension beyond its known cardiac preload reducing ability.